2016
DOI: 10.1038/srep33604
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of fibroblast growth factor receptor 4 polymorphisms on biochemical recurrence after radical prostatectomy in a Chinese population

Abstract: Fibroblast growth factor receptor 4 (FGFR4) is a transmembrane receptor with ligand-induced tyrosine kinase activity and is involved in various biological and pathological processes. Several polymorphisms of FGFR4 are associated with the incidence and mortality of numerous cancers, including prostate cancer. In this study, we investigated whether the polymorphisms of FGFR4 influence the biochemical recurrence of prostate cancer in Chinese men after radical prostatectomy. Three common polymorphisms (rs1966265, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The FGFR4 SNP rs351855, corresponding to the Gly388Arg substitution, is an important polymorphism that is biologically functional and can affect the transmembrane domain of the protein . FGFR4 is overexpressed in many cancers, including gastric cancer, non‐small cell lung cancer, colorectal cancer, and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The FGFR4 SNP rs351855, corresponding to the Gly388Arg substitution, is an important polymorphism that is biologically functional and can affect the transmembrane domain of the protein . FGFR4 is overexpressed in many cancers, including gastric cancer, non‐small cell lung cancer, colorectal cancer, and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs351855 (CC/TT) was an independent prognostic indicator in our multivariate analysis (Table ), and Kaplan‐Meier analysis revealed that the survival rate of patients was decreased along with an increase in MAF (Figure ), in accordance with previous studies. In addition, Chen et al proved that biochemical recurrence‐free survival time decreases along with an increase in A allele frequency in prostate cancer. Spinola et al found that lung adenocarcinoma patients carrying the Arg allele (Arg/Arg or Gly/Arg) had a significantly higher occurrence of death compared to those carrying the Gly allele, and non‐Hodgkin lymphoma G allele carriers had a significantly longer survival time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heinzle et al [ 20 ] demonstrated that among patients with colorectal cancer, FGFR4 A allele carriers had a five-fold higher risk of tumors that were stage II or higher. Chen et al [ 21 ] reported that patients with the FGFR4 SNP rs351855 AA or AG genotype exhibited a poorer biochemical recurrence-free survival than did those with the GG genotype. Therefore, the SNP rs351855 of FGFR4 polymorphism might provide a basis for surveillance programs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FGFR4 Arg388 allele has been linked to advanced stage and more frequent lymph node (LN) metastases than the wild-type homozygote (Gly/Gly) in the cohorts of CRC ( 12 ), BC ( 12 , 34 ), PC ( 15 ), and LC ( 18 ). It has also been implicated in reducing disease-free survival or overall survival in patients with BC ( 12 , 35 ), HNSCC ( 24 , 25 , 36 ), GC ( 37 , 38 ), PC ( 39 ), CRC ( 40 ), and LC ( 9 , 41 ). Interestingly, Serra et al.…”
Section: Introductionmentioning
confidence: 99%